2019
DOI: 10.1113/jp277609
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of astrocytic intracellular Ca2+ mobilization

Abstract: Astrocytes generate robust intracellular Ca 2+ concentration changes (Ca 2+ signals), which are assumed to regulate astrocytic functions that play crucial roles in the regulation of brain functions. One frequently used strategy for exploring the role of astrocytic Ca 2+ signalling is the use of mice deficient in the type 2 inositol 1,4,5-trisphosphate receptor (IP 3 R2). These IP 3 R2-knockout (KO) mice are reportedly devoid of Ca 2+ mobilization from the endoplasmic reticulum (ER) in astrocytes. However, they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 108 publications
(108 reference statements)
0
22
0
Order By: Relevance
“…Although MAMs are enriched in ER-localized inositol triphosphate type 2 (IP3R2) receptors 55 , a previous study has shown that astrocytic mitochondrial Ca 2+ fluxes are independent of IP3R2 23 . An alternative possibility is that Ca 2+ transfer from the ER to mitochondria occurs through other isoforms of IP3 receptors, and ER-localized ryanodine receptors (RyRs) 56,57 . Thus, we surmise that spontaneous Ca 2+ events in astrocytic mitochondria occur at MAMs, and most likely involve Ca 2+ transfer to mitochondria via ER-localized isoforms of IP3 and RyR receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Although MAMs are enriched in ER-localized inositol triphosphate type 2 (IP3R2) receptors 55 , a previous study has shown that astrocytic mitochondrial Ca 2+ fluxes are independent of IP3R2 23 . An alternative possibility is that Ca 2+ transfer from the ER to mitochondria occurs through other isoforms of IP3 receptors, and ER-localized ryanodine receptors (RyRs) 56,57 . Thus, we surmise that spontaneous Ca 2+ events in astrocytic mitochondria occur at MAMs, and most likely involve Ca 2+ transfer to mitochondria via ER-localized isoforms of IP3 and RyR receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of GPCRs that stimulates phospholipase C-dependent production of InsP 3 serves as both a source of signaling and an enhancer of the integrative potential of astrocytic branches. In addition, Ca 2+ release from ER can be mediated by InsP 3 receptor-independent mechanisms, or Ca 2+ may be released from mitochondria in astrocytic branches [54,55]. In summary, there Box 2.…”
Section: Ionic Signaling In Branches and Leafletsmentioning
confidence: 99%
“…Thus, "artificial" induction of Ca 2+ rise in astroglial cells might mimic the activation achieved by ligands of GPCRs, K + , ATP, or cytokines. As a result of activation, extracellular K+ concentrations transiently rise, astrocytes release gliotransmitters and change their mitochondrial activity and proliferative status [172][173][174]. Actually, this is a principle of optogenetic photostimulation of astroglial cells expressing ChR2 or optoGPCRs under the astroglial promoters (i.e., GFAP), which recently appeared as a new approach to control brain activity [175][176][177][178].…”
Section: Optogenetic Targeting Of Gfap + Cells In the Neurogenic Niche: Established And Prospective Approaches To Cells Activation And Simentioning
confidence: 99%